Förgiftningar hos hund och katt - Niemi, Caroline (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Cats and dogs are often unattended by their owners both indoors and outdoors, and therefore there is always a risk that they will get hurt. In the past, poisoning cases was considered unusual, but nowadays they are considered more common. As a veterinary nurse, it is important to know the common symptoms of poisoning, especially when working with emergency veterinary care. A very essential part of the profession as a veterinary nurse is to inform pet owners about the potentially dangerous substances and how poisonings can be prevented.